Carbon emission and export from the Ket River, western Siberia - Lim, Artem G.; Kritskov, Ivan V.; Vorobyev, Sergey N. биолог; Korets, Mikhail A.; Kopysov, Sergey G.; Shirokova, Liudmila S.; Karlsson, Jan; Pokrovsky, Oleg S. (Biogeosciences)
Despite recent progress in the understanding of the carbon (C) cycle of Siberian permafrost-affected rivers, spatial and seasonal dynamics of C export and emission from medium-size rivers remain poorly unknown. Here we studied one of the largest tributaries of the Ob River, the Ket River (watershed = 94,000 km²) which drains through virtually pristine dense taiga forest of the boreal zone in western Siberian Lowland (WSL). We combined continuous in-situ measurements of carbon dioxide (CO2) concentration and flux (FCO2), with methane (CH4), organic and inorganic C (DOC and DIC, respectively), particulate organic C and total bacterial concentrations over a 834-km transect of the Ket River main stem and its 26 tributaries during spring flood and 12 tributaries during summer baseflow. The CO2 concentration was lower and less variable in the main stem (2000 to 2500 µatm) compared to that in tributaries (2000 to 5000 µatm). The methane concentrations in the main stem and tributaries was a factor of 300 to 1900 (flood period) and 100 to 150 (baseflow period) lower than that of CO2. The FCO2 ranged from 0.4 to 2.4 g C m-2 d -1 43 in the main channel and from 0.5 to 5.0 g C m-2 d -1 44 in the tributaries, being the highest during August in tributaries and weakly dependent on season in the main channel. Only during summer baseflow, the DOM aromaticity, bacterial number, and needleleaf forest coverage of the watershed positively affected CO2 concentrations and fluxes. We hypothesize that the relatively low variability in FCO2 is due to flat homogeneous (bog and taiga forest) landscape that results in long water residence times and stable input of allochthonous DOM, which dominate the FCO2. In summer baseflow, the DIC input from deeper flow paths might also contribute to CO2 emission. The open water period (May to October) C emission from the Ket River basin was estimated to 127±11 Gg C y-1 51 which is lower than the lateral C export during the same period. Although this estimated C emissions contain uncertainties, stressing the need of better constrained FCO2 and water coverage across seasons, we considered it conservative which emphasize the important role of WSL rivers for release of CO2 to the atmospher